Integration of the territory in west central area interinfluence: a proposal under regionalisation (2014)
This paper presents the results of a research study, in which it is proposed land integration of several municipalities under RED scheme Microregional for sustainable development will, leading a form of regionalization adequate for managing local development in the territory of Central Western inter-influence justified in the process of territorial ordering and decentralization. This proposal was obtained, first from a general analysis of the region, and second after conducting a feasibility study to determine the key variables in the consolidation of a region and finally after a review and selected bibliography on the subject of planning in Colombia.